Investigation on the thermal performance of spiral wound heat exchanger for the superfluid helium cryogenic system. (April 2021) - Zhang, Jun; Song, Chen-chen; Niu, Xiao-fei; Wang, Xian-jin; Bai, Feng; Bi, Hai-lin
Highlights: Test rig of heat exchanger in superfluid helium cryogenic system is constructed. Flow and heat transfer process in spiral wound heat exchanger is simulated. Influence of fins structure on the thermal performance is investigated. Abstract: Spiral wound heat exchanger has compact structure, good thermal performance per volume and simple manufacture process. It is the key equipment for the superfluid helium cryogenic system, which is able to recover the cold capacity and improve the refrigeration effectiveness. To investigate the influence of fins structure on the thermal performance of spiral wound heat exchanger is essential for its structure design. This study combines experiment and CFD simulation methods, which means a performance test rig of heat exchanger in superfluid helium cryogenic system is designed and constructed, and a numerical simulation method of flow and heat transfer in heat exchanger is established with working medium as helium in the temperature range of 2 K 4.2 K. In this study, the heat transfer effectiveness and pressure drop in shell domain of spiral wound heat exchanger is obtained with the number of fins in the range of 40 135, area of single fin in the range of 669 mm 2 1885 mm 2, area ratio in the range of 0% 36%. Furthermore, the mechanics of fins structure affect the thermal performance of spiral wound heat exchanger is explored. This study provides reliable method and experimental data for the structure design and thermal performances analysis of spiral wound heat exchanger with helium in the temperature range of 2 K 4.2 K. It is significant for the design and experimental test of superfluid helium cryogenic system.